HISTORICAL NAMES: DISCUSSION AND APPROACHES (AS AN EXAMPLE OF “BABURNOMA” AND “SHAJARAI TURK”) - Abdullaeva, Marguba (International Journal of Psychosocial Rehabilitation, 2020)
– The information about the historical figures presented in the historical and prose works is an important source for the study of the social, literary and historical processes of that time. In particular, the portraits of rulers and princes, creators, representatives of religion and mysticism, sovereign and princesses presented in the works of "Baburnoma" and "Shajarai Turk" are important in the study of literary and cultural life of the 16th and 17th centuries. This study provides a comparative analysis of the attitude and interpretation of Zahiriddin Muhammad Babur and Abulgazi Bakhodirhan in their writings. It provides an in-depth analysis of the author's "I" and worldview in historical prose. Babur has developed a unique way of describing the life and activities of rulers. Firstly, he mentioned the rulers, such as "Valodat va nasabi", "Shakl va shamoyil", "Axloq va avtori", "Masof va urushlari", "Viloyati", "Avlodi", "Xavotun va sarori", "Umarosi" under the headings he describes them in order. Abulgazi lists seven descendants, such as Babur, in informing the rulers. He gives each of the seven fathers a Mongolian version. Abulgazy uses a very simple style to describe the "Haft pusht" without following Babur. The ethnography of the names of the descendants of the Turkic peoples is also associated with historical figures - rulers. In Babur and Abulgazi's relationship to historical figures, we can see that the author's "I" is the leading figure. Because the authors portray the historical figure in their imagination and outlook. This provides the basis for the view that the character of the historical figure is reflected in the author's own viewpoint and worldview. In “Baburnoma”, Babur treats creative people as a critic. He reveals his inner character through the visible signs of the creator. On this basis, the poet evaluates his personality, his works and his work in general. Vividly expresses character traits. Abulgazi’s book "Shajarai Turk" contains a comprehensive description of the rulers, the prominent figures of each era, who play an important role in the socio-political life. The author, for his own purposes, did not consider it necessary to represent artists and creative people. However, whether the author wants it or not, he presents   several   (including   himself)   creators   to   the   story's   interpretation. In general, the author's "I" priority in relation to kings and princes, literature and art, historical reality in this research, religion and mysticism has been studied scientifically.